2020
DOI: 10.1002/pc.25483
|View full text |Cite
|
Sign up to set email alerts
|

An effective surface modification of UHMWPE fiber for improving the interfacial adhesion of epoxy resin composites

Abstract: Ultra high molecular weight polyethylene (UHMWPE) fiber composite was reinforced by coating a functional layer on the surface of the UHMWPE fiber to improve interfacial adhesion between the fiber and the resin matrix. In this work, tannic acid (TA)‐Na+ composite modified UHMWPE fiber was used to improve moisture wettability and adhesion between the fiber and the resin. This approach had the advantages of being green, sustainable, lossless, low‐cost, and industrialized. The surface characteristics of UHMWPE fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Smooth surfaces in hip joint bearing pairs generate less wear, increasing the life of implantation. [ 55 ]…”
Section: Resultsmentioning
confidence: 99%
“…Smooth surfaces in hip joint bearing pairs generate less wear, increasing the life of implantation. [ 55 ]…”
Section: Resultsmentioning
confidence: 99%
“…The large number of phenolic hydroxyl groups in the structure makes it easy for tannic acid to form stable nanofilms on substrates [43] . The adhesion of TA coating can improve the mechanical meshing ability, wettability and bonding force of UHMWPE fiber surface, thus improving the interface properties of composites [42] .…”
Section: Coatingmentioning
confidence: 99%
“…The tannic acid (TA) -Na + metal complex coating was used to modify UHMWPE fibers [42] . The large number of phenolic hydroxyl groups in the structure makes it easy for tannic acid to form stable nanofilms on substrates [43] .…”
Section: Coatingmentioning
confidence: 99%
“…Wang et al demonstrated the use of a tannic acid-Na + coating to introduce reactive functional groups onto the surface of UHMWPE fibers to improve the interfacial shear strength (IFSS) of the UHMWPE composites by 43.3%, compared to untreated composites. [24] Mohammadalipour et al grafted glycidyl methacrylate (GMA) onto the UHMWPE fiber and embedded the fibers into a nano-clay/epoxy resin and demonstrated a 229% increase in IFSS measured using micro-droplet testing. [25] Ahmadi et al determined that the addition of multiwalled carbon nanotubes to a GMA and amino-thiol chemicaltreated fiber can yield a 336% improvement in IFSS.…”
Section: Introductionmentioning
confidence: 99%